Answer :

On cross multiplying the given equation, we get,


3(3y + 5) = 5(3 – 7y)


9y + 15 = 15 – 35y


9y + 35y = 15 – 15


44y = 0


y = 0


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)

<span lang="EN-USMHB - Mathematics (Old)